Towards methods for evaluating and communicating participatory design: A multimodal approach. Issue 94 (October 2016) - Malinverni, Laura; Mora-Guiard, Joan; Pares, Narcis
Abstract: Participatory Design (PD) has been proposed as a useful strategy to address pitfalls in the design of serious games for children with special needs. Nonetheless, methodological weaknesses in the analysis of the results of PD workshops may hinder its effectiveness in providing useful and robust design contributions and facilitating communication in multidisciplinary teams. To address this issue we propose the use of multimodal analysis to evaluate participants' contributions during PD workshops. We present an analysis that was applied in an informant workshop with autistic children, aimed at refining the design of a serious game based on Full-Body Interaction. Results show that multimodal analysis constitutes an effective and coherent method to capture and analyze users' contributions across a wide range of semiotic resources, thus extending the richness of insights that can be derived from a PD workshop and communicated to the rest of the team. Furthermore, the analysis allowed the identification of fundamental design questions, thus offering a robust empirical ground for supporting dialogue and reflection between multiple stakeholders. Highlights: Use of Multimodal Analysis to analyze users' contributions in Participatory Design. Case study with 4 children in Autistic Spectrum Disorder. Multimodal analysis effectively grasped contributions across different resources. Usefulness for guiding design of Serious Games in interdisciplinary teams.